2015
DOI: 10.1016/j.archger.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Is knee extension strength a better predictor of functional performance than handgrip strength among older adults in three different settings?

Abstract: Handgrip and knee extension strength are both important predictors of functional performance in older adults. In assisted living facilities only, knee extension strength was clearly more predictive than handgrip strength. Both cut-off values appear to be highly sensitive to screen for functionally relevant muscle weakness in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
3
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 41 publications
5
47
3
6
Order By: Relevance
“…Hand grip strength is an important component of the diagnostic algorithm of sarcopenia and a well-known predictor of lower extremity functional capacity in the geriatric population (3,23,24). Consistent with previous findings, HGS was associated with lower extremity performance tests in our study.…”
Section: Discussionsupporting
confidence: 82%
“…Hand grip strength is an important component of the diagnostic algorithm of sarcopenia and a well-known predictor of lower extremity functional capacity in the geriatric population (3,23,24). Consistent with previous findings, HGS was associated with lower extremity performance tests in our study.…”
Section: Discussionsupporting
confidence: 82%
“…Hierbei gilt die isokinetische Dynamometrie, d. h. die Messung über einen dynamischen Bewegungsablauf mittels unterschiedlicher Winkelgeschwindigkeiten (▶ Abb. 1), als Goldstandard [37].…”
Section: Knee Extension Peak Torqueunclassified
“…Functionally, dorsiflexion strength is important in gait mechanics, as it is a vital component that assists with foot clearance during the swing phase of the gait cycle. If an individual is unable to perform the necessary dorsiflexion secondary to a pathology, the risk of unsuccessful toe clearance and falls increases [23,24]. The falls could inevitably lead to increased health problems, decreased independence, and decreased quality of life [12,17].…”
Section: Significant Clinical Impairment Measures: Handheld Dynamometmentioning
confidence: 99%
“…Grip strength is imperative to daily activities and research has shown a strong correlation to grip strength and quality of life [11]. Grip strength is said to have a strong correlation with functional performance 24 and is a predictor of functional decline, nursing home placement, and even mortality [25]. As one example, it has been shown that female ALF residents that fall generally have weaker handgrip strength as compared to their female ALF non-faller counterparts [26].…”
Section: Significant Clinical Impairment Measures: Handheld Dynamometmentioning
confidence: 99%